Utility of telemedicine in sub‐Saharan Africa during the COVID‐19 pandemic. A rapid review. Issue 5 (2nd November 2021) - Chitungo, Itai; Mhango, Malizgani; Mbunge, Elliot; Dzobo, Mathias; Musuka, Godfrey; Dzinamarira, Tafadzwa
Abstract: Telemedicine is the use of technology to achieve remote care. This review looks at the utility of telemedicine during the pandemic, period March 2020 to February 2021. Eleven articles met inclusion criteria. There was moderate use of telemedicine in sub‐Sahara Africa during the pandemic, however, there were also some limitations. Benefits of telemedicine include continuing medical service provision, connecting relatives with loved ones in quarantine, education, and awareness of mental health issues, and toxicovigilance and infection control. Challenges to the implementation of telemedicine on the continent were lack of supporting telemedicine framework and policies, digital barriers, and patient and healthcare personnel biases. To address these challenges, this article proposes the development of policy frameworks that fosters telemedicine use by all stakeholders, including medical insurance organizations, the introduction of telemedicine training of medical workers, educational awareness programs for the public, and improvement of digital platforms access and affordability. Abstract :